Level and determinants of knowledge of symptomatic knee osteoarthritis among railway workers in Malaysia - Ganasegeran, K.; Menke, J.M.; Ramaswamy, V.M.C.; Manaf, R.A.; Al-Absi, A.M.; Al-Dubai, S.A.R. (Hindawi Publishing Corporation, 2014)
Background. Symptomatic knee osteoarthritis, an ancient malady greatly impairing modern population quality of life, has stimulated global attention to find effective modes of prevention and intervention. Purpose. This study aimed to assess factors affecting knowledge of symptomatic knee osteoarthritis (knee OA) among Malaysian railway workers. Methods. A cross-sectional study was conducted among 513 railway workers involving eight major states within Peninsular Malaysia using population-based sampling. The assessment instrument was a face-validated, prepiloted, self-administered instrument with sociodemographics and knowledge items on knee OA. Results. Mean (+/- SD) age of the respondents was 41.4 (+/- 10.7), with the majority aged 50 years or older (34.9%). Of the total respondents, 53.6% had low levels of knowledge of knee OA disease. Multivariate analysis found that four demographic predictors, age >= 50 years, family history of knee OA, self-awareness, and clinical diagnosis of the disease entity, were significantly associated with knowledge scores. Conclusion. The finding of a low level knee OA knowledge among Malaysian railway workers points to an urgent need for massive information to be disseminated among the workers at risk to foster primary prevention and self-care.